WATER QUALITY MANAGEMENT IN INTENSIVE AQUACULTURE OF VANNAMEI Shrimp (Litopenaeus vannamei) at PT. ANDULANG SHRIMP FARM - Lusiana BR Ritonga (Universitas Tidar, 2021)
Vaname shrimp (Litopenaeus vannamei) is one of the commodities that is very promising for aquaculture and is a prima donna because of the high international market demand so that vaname shrimp production needs to be increased. Increasing shrimp production can be done with a high stocking density system. However, one of the drawbacks of this system is that it can reduce water quality because this system requires high feeding. Declining water quality will cause stress to the shrimps and cause diseases that cause failure in shrimp enlargement, it is necessary to manage water quality properly and appropriately. The main parameters observed in this study were stocking density, feed management and water quality monitoring. Water quality during the observation is still in the normal range of brightness, 25-90 cm, temperature ranges between 27-31.8.0C, pH between 67.1-8.7, salinity 19-31 ppt, dissolved oxygen between> 4.03 -5.60 mg / l, alkalinity ranges from 74-154 mg / l, TOM ranges from 24.8-90.0 mg / l, ammonium ranges from 0.5-5 mg / l, nitrites range between 0.5 -18 mg / l, and phosphate ranges from 0.25-18 mg / l.